2019
DOI: 10.1093/toxsci/kfz047
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Metabolism of an Environmentally Relevant Phthalate Mixture

Abstract: Phthalates are synthetic chemicals with widespread human exposure due to their use as additives in consumer products. Phthalate diesters are hydrolyzed in the environment and in the body to monoesters that may be more toxic than the parent compounds. This study tested the hypothesis that adult mouse antral follicles, but not neonatal ovaries, are able to metabolize an environmentally relevant mixture of phthalates. Whole neonatal ovaries and isolated adult antral follicles from CD-1 mice were cultured in media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…This variability might suggest that the follicular environment has some capability of metabolizing these EDCs (esterase activity), which may vary between subjects and among ethnic groups (enzymes polymorphisms), although this aspect should be deepened by further studies. Warner et al, (2019) showed that the mouse ovary can metabolize a mixture of phthalates with varying metabolizing capacity at different stages of folliculogenesis [ 2 ]. However, together with a different exposure profile deriving from a different geographical area, a different clearance rate could explain the different concentrations of phthalate esters among these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability might suggest that the follicular environment has some capability of metabolizing these EDCs (esterase activity), which may vary between subjects and among ethnic groups (enzymes polymorphisms), although this aspect should be deepened by further studies. Warner et al, (2019) showed that the mouse ovary can metabolize a mixture of phthalates with varying metabolizing capacity at different stages of folliculogenesis [ 2 ]. However, together with a different exposure profile deriving from a different geographical area, a different clearance rate could explain the different concentrations of phthalate esters among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates are mainly used as a plasticizer in polyvinylchloride (PVC) products and are produced through esterification with different substituents of phthalic anhydride. However, phthalates are a broad group of substances and they are classified as short-chain (low molecular weight: diethyl phthalate, di-butyl phthalate, and di-isobutyl phthalate) or long-chain (high molecular weight: benzyl-butyl phthalate, di(2-ethylhexyl) phthalate, and di-isononyl phthalate) phthalates [ 2 ]. The most common types of phthalates include di(2-ethylhexyl) phthalate (DEHP), dibutyl phthalate (DBP), dibenzyl phthalate (DBzP), diethyl phthalate (DEP) and dimethyl phthalate (DMP).…”
Section: Introductionmentioning
confidence: 99%
“…This study examined media and protein directly from the manufacturer and not after incubation over varying lengths of time. An incubation period may influence the ratio of DEHP to MEHP because the conversion of DEHP to MEHP requires unspecific ligases that are present in RBCs (41) and are possibly present in gametes or embryos (56). Overall, this work established a foundation for further inquiry about potential contamination of proteins supplied to gamete or embryo cultures.…”
Section: Figurementioning
confidence: 87%
“…Urinary MBP, MEHP and MEP contributed over 95% of total phthalate exposure, whereas MBP and MEHP were dominantly compounds in serum and cord blood samples. Short-chain phthalates, like DEP and DMP, were rapidly metabolized to their metabolites in a few hours [ 62 ], which instantly excreted to urine and may not cause significant placenta transportation [ 63 , 64 ]. For long-chain phthalates with longer half-lives, like DBP and DEHP, continuous exposure to these phthalates through food and food packaging materials [ 18 , 65 ] are possible reasons that MBP and MEHP were both dominant compounds in serum and urine samples.…”
Section: Discussionmentioning
confidence: 99%